XXXVII Biennale Venezia 1976 - Ungheria. - XXXVII Biennale Venezia, 1976 - pav. Hongarije (Venezia : La Biennale di Venezia, 1976)
Balint, Endre ; Barcsay, Jeno ; Czobel, Belo ; Deim, Pol ; Ferenczy, Beni ; Ferenczy, Karoly ; Ferenczy, Noemi ; Fenyes, Adolf ; Kmetty, Janos ; Korniss, Dezso ; Kovacs, Margit ; Szanto, Piroska ; Vajda, Lajos ; etc.
XXXVII Biennale Venezia 1976 - Ungheria, 14.07 - 10.10.1976
Italiaans
kunstcatalogus
Keywords: Hongarije